2015
DOI: 10.1007/s40477-015-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section scar ectopic pregnancy: a clinical case series

Abstract: Cesarean scar implantation represents a rare, though growing subset of potentially life-threatening ectopic pregnancy. Because of the global increase in cesarean sections as well as the improved diagnostic abilities of transvaginal ultrasound, incidence rates have continued to rise since the first reported case in 1978. Uterine rupture and catastrophic hemorrhage can ensue when diagnosis is delayed. Additionally, a higher rate of concurrent trophoblastic myometrial invasion may increase the incidence of retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Postmenstrual brown spotting and secondary infertility are the main clinical manifestations in gynecology offices . Ectopic pregnancy at the site, like CS scar pregnancy, could be another serious complication, which could be life‐threating because of CS uterine rupture and massive haemorrhage …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmenstrual brown spotting and secondary infertility are the main clinical manifestations in gynecology offices . Ectopic pregnancy at the site, like CS scar pregnancy, could be another serious complication, which could be life‐threating because of CS uterine rupture and massive haemorrhage …”
Section: Discussionmentioning
confidence: 99%
“…5 Ectopic pregnancy at the site, like CS scar pregnancy, could be another serious complication, which could be life-threating because of CS uterine rupture and massive haemorrhage. 6 The etiopathogenesis of the CSD remains unknown. Fabres et al 7 have suggested that the defect might be bound up with the suturing technique when it is performed in relation to labor and uterine cervical changes.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of cesarean section scar pregnancy can be made when a gestational sac is in the lower uterine segment, anterior to the endometrial stripe, with less than 5 mm of overlying myometrium (Fig. ) . In 86% of cases, MRI identifies a cesarean scar defect, and demonstrates various degrees of protrusion of a low‐lying gestational sac through the defect .…”
Section: Acute Gynecologic Conditions Related To Pregnancymentioning
confidence: 99%
“…They have overviewed the main problems associated with increased rate of cesarean section [8][9][10]. It seems the main reason of repeat cesarean sections is the uterine scar dehiscence after previous cesarean section, which can produce rupture of the uterus through dehiscence scar during pregnancy [43] or delivery in about 70% of cases. Authors believed that disturbances of wound healing and uterine wall repair are the main causative factor for scar deficiency due to: 1) inappropriate surgical procedure during abdominal birth; 2) inaccurate suturing; 3) pathological bleeding; 4) inflammation of uterine wall; 5) postpartum intrauterine procedures (repeat curettage of uterine cavity).…”
Section: Dr David Chuderland From Genesort Ltdmentioning
confidence: 99%